Possible violations of the Haeberli rules in reaction (d,p) on 1p shell nuclei at low energy - Sarana, V.D.; Lutsay, N.S.; Shlyakhov, N.A. (Вопросы атомной науки и техники, 2015)
In this paper we investigate the possibility of simultaneous description of the angular distributions of the cross section, the vector polarization and the vector analyzing power with DWBA, using various modifications deuteron Z-potentials and Perey, previously experimentally observed violations of rules Haeberli in the low-energy deuterons on the example of the reaction ⁹Be(d,p)¹⁰Be. Found that using DWBA this case can be described as a violation of the rules Haeberli at the low energy. Досліджується можливість одночасного опису кутових розподілів перерізу, векторної поляризації і векторної аналізуючої здатності в рамках БПІВ, з використанням різних модифікацій дейтонного Z-потенціалу і потенціалу Перея, раніше экспериментально спостережуваних порушень правила Хаберлі в області малих енергій дейтронів на прикладі реакції ⁹Be(d,p)¹⁰Be. Знайдено, що за допомогою БПІВ можна описати порушення правила Хаберлі при низькій енергії. Исследуется возможность одновременного описания угловых распределений сечения, векторной поляризации и векторной анализирующей способности в рамках БПИВ, с использованием различных модификаций дейтонного Z-потенциала и потенциала Перея, ранее экспериментально наблюдаемых нарушений правила Хаберли в области малых энергий дейтронов на примере реакции ⁹Be(d,p)¹⁰Be. Найдено, что с помощью БПИВ можно описать нарушение правила Хаберли при низкой энергии.